miR-20b, miR-296, and Let-7f Expression in Human Adipose Tissue is Related to Obesity and Type 2 Diabetes. - Gentile, Adriana Mariel; Lhamyani, Said; Coín-Aragüez, Leticia I.; Clemente-Postigo, María Mercedes; Oliva Olivera, Wilfredo; Romero-Zerbo, Silvana Yanina; García Serrano, Sara; García-Escobar, Eva; Zayed, Hatem; Doblado, Esther; Bermúdez Silva, Francisco Javier; Murri, Mora; et al. (Wiley, 2019)
Objective: This study aimed to analyze the potential association of different microRNA (miRNA) moleculeswith both type 2 diabetes (T2D) and obesity and determine their target genes.Methods: Quantitative PCR was used to analyze the miR-20b, miR-296, and Let-7f levels in human visceraland subcutaneous adipose tissues (ATs) in relation to obesity and T2D, miRTarBase 4.0 was used for valida-tion of target genes, and the Protein Analysis Through Evolutionary Relationships (PANTHER) ClassificationSystem and the Database for Annotation, Visualization and Integrated Discovery (DAVID) were used to an-notate the biological processes of the predicted targets.Results: In AT, miR-20b, miR-296, and Let-7f levels were significantly different between normoglycemicsubjects and those with T2D. In visceral adipose tissue, miRNA levels were higher in normoglycemic/obesitysamples than in T2D/obesity samples. miR-20b, miR-296, and Let-7f target genes that showed significantdifferences in both ATs in relation to obesity and T2D were CDKN1A, CX3CL1, HIF1A, PPP2R1B, STAT3, andVEGFA. These genes are known to be principally involved in the vascular endothelial growth factor (VEGF)and WNT pathways.Conclusions: This study provides experimental evidence of the possible correlation between AT miR-20b,miR-296, and Let-7f with obesity and T2D, which might involve vascular endothelial growth factor and WNT-dependent pathways that are regulated by six different genes, suggesting a novel signaling pathway thatcould be important for understanding the mechanisms underlying the AT dysfunction associated with obe-sity and T2D
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/4029
Keywords: Obesidad - Investigación; Diabetes - Investigación; Type 2 diabetes; Obesity; microRNA (miRNA); Adipose tissues